1999
DOI: 10.1002/(sici)1096-9071(199909)59:1<78::aid-jmv13>3.3.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Ability of yeast Ty-VLPs (virus-like particles) containing varicella-zoster virus (VZV)gE and assembly protein fragments to induce in vitro proliferation of human lymphocytes from VZV immune patients

Abstract: Yeast Ty virus-like particles (VLPs) containing viral protein inserts have previously been shown to be potent immunogens, inducing both humoral and cell mediated immunity (CMI). The antigenicity of hybrid VLPs containing fragments of the varicella-zoster virus (VZV) gE protein or the assembly protein (AP) was assessed by lymphocyte proliferation. Peripheral blood mononuclear cells (PBMCs) from patients with a recent natural VZV infection were stimulated in vitro with VZV-VLPs together with control antigens. PB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…These results suggest that gH:gL, gB, and gE:gI induce cellular immunity to VZV and each glycoprotein. Although gE:gI and gB induce cellular immunity after subcutaneous or intramuscular injection [Garcia-Valcarcel et al, 1997;Welsh et al, 1999;Kutinova et al, 2001], there is no report showing that gH:gL is a stimulator for cellular immunity to VZV or itself on subcutaneous or intramuscular injection. It was then determined more precisely whether nasal coadministration of gH:gL and the toxin induced cellular immunity to VZV or gH:gL.…”
Section: Il-2 and Il-4 Production By Spleen Cells From Mice Immunizedmentioning
confidence: 99%
See 1 more Smart Citation
“…These results suggest that gH:gL, gB, and gE:gI induce cellular immunity to VZV and each glycoprotein. Although gE:gI and gB induce cellular immunity after subcutaneous or intramuscular injection [Garcia-Valcarcel et al, 1997;Welsh et al, 1999;Kutinova et al, 2001], there is no report showing that gH:gL is a stimulator for cellular immunity to VZV or itself on subcutaneous or intramuscular injection. It was then determined more precisely whether nasal coadministration of gH:gL and the toxin induced cellular immunity to VZV or gH:gL.…”
Section: Il-2 and Il-4 Production By Spleen Cells From Mice Immunizedmentioning
confidence: 99%
“…In contrast, in the cellular immune response, these glycoproteins show a positive reaction in the order, gH:gL, gB, and gE:gI in skin tests in guinea pigs infected by VZV [Giller et al, 1989;Sato et al, 1998]. Subcutaneous immunization with gE:gI and gB also induced cellular immunity to VZV and each glycoprotein in guinea pigs [Garcia-Valcarcel et al, 1997;Welsh et al, 1999;Kutinova et al, 2001]. Therefore, gE:gI, gB, and gH:gL are important for their potential use as a candidate subunit vaccine.…”
Section: Introductionmentioning
confidence: 99%
“…The identity of which potentially immunogenic epitopes have been lost through removal of these haplotypes is complicated by evidence from i n vitro studies, which have shown that the host cellular and humoral responses recognize a broad range of immunodominant epitopes from the IE62 and several VZV glycoproteins. Furthermore, the responses can vary between individuals and are therefore thought to be governed by HLA genotype . Genetic heterogeneity has also been observed between vaccine lots from the same manufacturer (Table ), the explanation for which is less clear but might relate to variation in passage numbers of the Master Seed Stocks.…”
Section: Introductionmentioning
confidence: 99%